(untitled) (Journal of Bangladesh Institute of Planners, 2018)
The detrimental impact of automobiles in today’s contemporary world has revived the interest in pedestrian facilities to promote walking as a sustainable mode of transportation. There are no better alternatives than pedestrian facilities to ensure and promote sustainable urban transportation. Bangladesh, being a developing country, has an lack of proper policy guidelines regarding pedestrian facilities. Khulna being a major city of Bangladesh, due to lack of proper policy and legislation, is lacking pedestrian facilities even in the CBD area. This study aims to investigate the existing pedestrian facilities, evaluate their condition and fulfilment of pedestrian demand in Khulna CBD. The study is mainly explorative in nature and both quantitative and qualitative approach of research has been implied. The quality of the existing pedestrian facilities has been compared to the standards identified from the international policies. Based on the extensive policy review, this study considers footpath, crossings, kerb ramp, street furniture and street lights as the most indispensable for pedestrian facilities. The findings reflect on poor quality pedestrian facilities in Khulna CBD. Finally, some general guidelines are recommended to incorporate in the National Land Transport Policy to shift focus from wider road provision to pedestrian facility development in areas like Khulna CBD to promote walking and, therefore, to contribute towards transport sustainability and livability of the CBD area. JBIP, Vol. 11, 2018 (Printed in June 2020), pp. 157-169